FORMULASI SEDIAAN LIP BALM KOMBINASI PERASAN BUAH MENTIMUN (Cucumis sativus¬ L.) DAN BUAH JERUK NIPIS (Citrus aurantiifolia) SEBAGAI PENCERAH BIBIR - Micie Sariwating; Eunike Syamma R Waas (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2020)
Lip balm is a compound applied to lips that serve as moisturizer and brightening. The purpose of research is to know the combination of squeeze fruits and lime as brightening the lips and to know the formulation of a finely tuned combination of cucumbers and lime. This method of study is a quantitative study method. This type of research includes a formulation of lip balm with a concentration of flavor (cucumis sativus l.) and lemon (citrus aurantifolia) concentrations of 5%, 6% and 7%. With the base material at a cacao and cera flava. Available physical quality checkups include organic, homogenity, ph, diffusion, stability, temperance, and irritation. Studies show that a thick-fruit cucumber and a lemon can be formulated into a willing lip balm with 5% concentrations (f1), 6% (f2), 7% (f3) and have met requirements for the coveted, sticky point and no skin. The characteristics of the cucumber and the lime that make a good lip balm ready is third preparation because more of the color on the lips shows brightness as well as moisture